Preparations, Characterizations and Comparative Study on Electrochemical Performance of ZnO/SWNT and TiO2 /SWNT Nanocomposites - Mohd Shaifuddin,M.A.F.; Che Abdullah, C.A.; Ribut, S.H.; Rosli,N.S.; Mohd Zawawi, R. (Universiti Sains Islam Malaysia, 2024)
This work has successfully prepared and characterized the nanocomposite based metal oxides, Zinc Oxide and Titanium Dioxide (ZnO and TiO2) with Single-Walled Nanotubes (SWNTs). Metal oxides are well-known alternatives to graphite as anode materials for lithium-ion batteries, due to their ability of highly capacities. In this study, green synthesis ZnO and TiO2 were synthesized from Kaffir Lime and Ilmenite mineral respectively, and their composite is prepared in the presence of SWNTs. The as prepared ZnO/SWNT and TIO2/SWNTs composite have been characterized by field emission scanning electron microscope (FESEM), Raman, and electron dispersive X-ray (EDX). The result of FESEM and EDX shows the metal oxide nanoparticles with average size 11.3 ± 3.0 nm was successfully deposited onto the SWNT. Electrochemical characterization of the prepared nanocomposites was carried out using cyclic voltammetry, and galvanostatic charge/discharge tests. The main difference found between these two nanocomposite is the internal resistance, thus giving specific capacitance 3.56 F/g and 0.78 F/g for SWNT/TiO2 and SWNT/ZnO respectively. The investigation highlights the importance of anchoring of green synthesis metal oxides nanoparticles on SWNTs for maximum utilization of electrochemically active ZnO, TiO2 and carbon nanotubes (CNTs) for energy storage application.